WILLIAMSON, R. e Diego, F. Verbo e imagen en la telenovela mexicana. NOVA York, Ottawa e Toron to: LEGAS, 2005, 347 Págs. - Lima, Elcivanni Santos (Cadernos de Linguagem e Sociedade, 2010)
WILLIAMSON, R. e Diego, F. Verbo e imagen en la telenovela mexicana. NOVA York, Ottawa e Toron to: LEGAS, 2005, 347 Págs.